1994
DOI: 10.1111/j.1445-2197.1994.tb02263.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Methods of Pancreas Transplantation in the Rat Using a Cuff Technique

Abstract: Two models of pancreas transplantation were examined in the rat with a view to choosing one for regular use in functional experiments. A cuff technique applied to the renal vessels of the recipient was used. The histology and endocrine functioning of whole pancreas-duodenal transplant (Tx) plus bladder drainage (drainage model), and the pancreatic duct ligated segmental pancreas Tx (ligated model) were examined. Syngeneic operations were performed using either Lewis or Wistar rats. Streptozotocin (STZ) 60mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Rat pancreas transplantation models with cuff techniques have been described previously, [12][13][14] with claimed advantages such as the elimination of clamping the systemic circulation, decreased ischemic time, and no bleeding after revascularization. In this study, we found mouse pancreas transplantation with cuff techniques to be extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Rat pancreas transplantation models with cuff techniques have been described previously, [12][13][14] with claimed advantages such as the elimination of clamping the systemic circulation, decreased ischemic time, and no bleeding after revascularization. In this study, we found mouse pancreas transplantation with cuff techniques to be extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Di¤er bir uygulamada da ekzokrin sekresyonun ba¤ırsak içerisine veya mesane içerisine yapılmasıdır. [8] Bu nakillerde ilk uygulamlarda greft dokusunda görülen pankreatit ve idrar kaça¤ı sorunu gelitirilen tekniklerle, doku reddi (rejeksiyonu) de immünosüpesif tedaviyle önlenmitir (ekil 1). komplikasyonlar Sıklıkla komplikasyonlar ameliyatı takip eder, tromboz, pankreatit, enfeksiyon, kanama ve doku reddi eklindedir.…”
Section: Pankreas Nakl‹ End‹kasyonlarıunclassified
“…Rat pancreas transplantation models with cuff techniques have been described previously, [12][13][14] with claimed advantages such as the elimination of clamping the systemic circulation, decreased ischemic time, and no bleeding after revascularization. In this study, we found mouse pancreas Figure 4.…”
Section: S Leementioning
confidence: 99%